2016
DOI: 10.1080/03081087.2016.1189494
|View full text |Cite
|
Sign up to set email alerts
|

On a conjecture for the signless Laplacian spectral radius of cacti with given matching number

Abstract: A connected graph G is a cactus if any two of its cycles have at most one common vertex. Let ℓ m n be the set of cacti on n vertices with matching number m. S.C. Li and M.J. Zhang determined the unique graph with the maximum signless Laplacian spectral radius among all cacti in ℓ m n with n = 2m. In this paper, we characterize the case n ≥ 2m+1. This confirms the conjecture of Li and Zhang (S.C. Li, M.J. Zhang, On the signless Laplacian index of cacti with a given number of pendant vetices, Linear Algebra Appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Chen and Zhou [5] investigated some upper bounds of the signless Laplacian spectral radius of cactus graphs. The signless Laplacian spectral radius of cacti with given matching number are obtained by Shen et al [17]. Some results for spectral radius on cacti with k pendant vertices are studied Wu et al [18].…”
Section: Introductionmentioning
confidence: 97%
“…Chen and Zhou [5] investigated some upper bounds of the signless Laplacian spectral radius of cactus graphs. The signless Laplacian spectral radius of cacti with given matching number are obtained by Shen et al [17]. Some results for spectral radius on cacti with k pendant vertices are studied Wu et al [18].…”
Section: Introductionmentioning
confidence: 97%
“…Let G be an n-vertex graph with vertex set V (G) = {v 1 , v 2 , • • • , v n } and edge set E(G), then the signless Laplacian matrix of G is defined as Q(G) = D(G) + A(G), where D(G) is a diagonal matrix of vertex degrees and A(G) is the adjacency matrix. Since its introduction, there have existed lots of investigations on the signless Laplacian spectrum (see [7,21] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [16] found the spectral radius of cacti with k-pendant vertices. Shen et al [17] studied the signless Laplacian spectral radius of cacti with given matching number.…”
Section: Introductionmentioning
confidence: 99%